Fenomena Periodesasi Masa Jabatan Kepala Desa Perspektif Fiqh Siyasah Dan Undang-Undang Nomor 6 Tahun 2014 Tentang Desa (Studi Di Desa Payaman Kecamatan Solokuro Kabupaten Lamongan) - Ahmad Syaiful Maarif; Abd. Hadi; Moh Sa’diyin (Universitas Sunan Drajat Lamongan, Indonesia, 2024)
Based on the results of interviews with several community leaders in Payaman Village, the researcher found that there was something different regarding the period of office of the Village Head in Payaman Village where the researcher found that the Village Head only had one opportunity to nominate himself as Village Head even though it was in accordance with the rules contained in Law Number 6 of 2014 states that Village Heads can be elected for a maximum of three terms of office, here researchers believe that there is a phenomenon that Village Heads only have one opportunity to nominate themselves as Village Head in Payaman Village. The objectives to be achieved in this thesis are: To find out what the phenomenon of the Village Head's term of office in Payaman Village, Solokuro District, Lamongan Regency, is like from the Siyasah Fiqh Perspective. In collecting data for this thesis, the author used the following techniques or methods: 1) Observation, 2) Interview, 3) Documentation. The data phenomenon process carried out by researchers is in the following steps: 1) Data reduction, 2) Data display or presentation of data, 3) Drawing conclusions or verification.